A prosthetic material for rhinoplasty and a preparation method thereof
The rhinoplasty prosthesis prepared by using materials such as titanium-nickel-copper alloy and solid silicone rubber particles has solved the problems of impact resistance and instability of the existing materials, achieved high elasticity and strength of the materials, and ensured biosafety and antioxidant properties, safe implantation and removal, reducing trauma and risk during plastic surgery.
Patent Information
- Application Number
- CN202211654826.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-12-22
AI Technical Summary
Existing rhinoplasty prosthesis materials are not impact-resistant, have unstable shapes, are difficult to remove, and cause trauma to patients, resulting in frequent repairs or replacements, increasing the risk and cost of the plastic surgery process.
Using titanium-nickel-copper alloy as the core, it covers solid silicone rubber particles, polycarbonate resin, vinyl silicone and other materials, and forms plastic colloids through heat treatment and mixing to improve the elasticity and strength of the material, and pass the secondary Press-molding to obtain rhinoplasty prosthetic material with good biocompatibility and antioxidant properties.
The material has good elasticity and strength, can stably support the nose bridge, resist impact and restore its original state, has good biosafety and anti-oxidation and degradability, can be safely implanted and removed at any time, reducing trauma and risk during plastic surgery.
Smart Images

Figure CN116077722B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rhinoplasty prosthesis materials, in particular to a prosthesis material for rhinoplasty and a preparation method thereof. Background Art
[0002] The rhinoplasty prosthesis materials currently used in the market are artificial materials mainly based on silicone or expanded polytetrafluoroethylene. Among them, silicone has become the main medical prosthetic rhinoplasty material because it is non-toxic and harmless, has relatively stable tissue compatibility, is easy to shape during the production process, and can be safely removed after implantation. However, silicone is limited by its inherent properties and has poor impact resistance. It is also prone to displacement and oxidative contracture deformation after implantation. This requires people to regularly repair or replace prosthetic materials, which not only frequently damages the body, but also invisibly increases the cost of plastic surgery. Expanded polytetrafluoroethylene has the characteristic of good compatibility with human tissues, but high compatibility is a double-edged sword. After a period of time, the expanded polytetrafluoroethylene is connected to the tissue and grows into the tissue. If you want to remove the prosthesis, it will not only cause greater trauma to the nasal tissue, but also cause problems such as accidental infection. Summary of the invention
[0003] The purpose of the present invention is to provide a prosthetic material for rhinoplasty to solve the technical problems in the prior art that the prosthetic material for rhinoplasty is not impact-resistant, the shape and effect of rhinoplasty are unstable, the prosthetic material cannot be removed at any time, and it causes great trauma to the patient.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] A prosthetic material for rhinoplasty is made of the following components in parts by weight: 50-70 parts of titanium-nickel-copper alloy, 90-115 parts of solid silicone rubber particles, 15-30 parts of polycarbonate resin, 18-36 parts of vinyl silicone resin, 7-18 parts of vinyl silicone oil, 0.5-2 parts of triethylene diammonium, 14-22 parts of glycerol, 5-20 parts of polyethylene glycol-1000, 3-5 parts of diisononyl phthalate, 1-5 parts of tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionate] pentaerythritol, and 0.1-0.5 parts of zinc pentachlorothiophenol, wherein the alloy contains 45-50% nickel, 45-55% titanium and 0-5% copper.
[0006] Preferably, a prosthetic material for rhinoplasty is made of the following components in parts by weight: 60-70 parts of titanium-nickel-copper alloy, 95-110 parts of solid silicone rubber particles, 20-25 parts of polycarbonate resin, 20-35 parts of vinyl silicone resin, 10-15 parts of vinyl silicone oil, 0.8-1.5 parts of triethylene diammonium, 18-22 parts of glycerol, 10-18 parts of polyethylene glycol-1000, 3-5 parts of diisononyl phthalate, 3-5 parts of pentaerythritol tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionate], and 0.2-0.5 parts of zinc pentachlorothiophenol, wherein the alloy contains 47-50% nickel, 47-53% titanium and 0-3% copper.
[0007] Preferably, a prosthetic material for rhinoplasty is made of the following components in parts by weight: 66 parts of titanium-nickel-copper alloy, 108 parts of solid silicone rubber particles, 23 parts of polycarbonate resin, 30 parts of vinyl silicone resin, 13 parts of vinyl silicone oil, 1.2 parts of triethylene diammonium, 20 parts of glycerol, 15 parts of polyethylene glycol-1000, 3 parts of diisononyl phthalate, 4 parts of pentaerythritol tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionate], and 0.25 parts of zinc pentachlorothiophenol, wherein the alloy contains 48% nickel, 50% titanium and 2% copper.
[0008] The present invention also provides a method for preparing a prosthetic material for rhinoplasty, which specifically comprises the following steps:
[0009] (1) Titanium, nickel and copper metal wires are melted by induction heating, extruded and spun, and then heat treated in a vacuum tube resistance furnace, kept warm for a period of time, and then slowly cooled to room temperature;
[0010] (2) Weigh the above-mentioned raw materials according to the above-mentioned mass fractions, crush the solid silicone rubber particles and place them in a blender, then continue to add polyethylene glycol-1000, glycerol, polycarbonate resin, vinyl silicone resin, vinyl silicone oil, and triethylene diammonium, heat to 158-165° C., mix evenly and stir for 0.25-1 h; then add diisononyl phthalate, tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionate] pentaerythritol, and zinc pentachlorothiophenol, stir at 120-150° C. for 0.5 h to obtain a mixture;
[0011] (3) The mixture obtained in step (2) is placed in a mixer and mixed at 1.2 MPa, and then transferred to the mold of step (1) to fully wrap the titanium-nickel-copper alloy, and subjected to secondary compression molding, and then slowly cooled to room temperature for demolding, and the prosthetic material can be obtained after sterilization.
[0012] Furthermore, the vinyl silicone resin is methyl vinyl MQ type silicone resin with a molecular weight of 2000.
[0013] Furthermore, the heat treatment temperature in step (1) is 450-600° C., and the insulation time is 0.5-1 h.
[0014] Furthermore, in step (3), the mixing temperature is 320-380° C., and the mixing time is 0.25-0.5 h.
[0015] Furthermore, in step (3), the pressing temperature is 200-350° C., the pressing pressure is 20-60 MPa, and the pressing time is 5-10 h.
[0016] The present invention has the following advantages:
[0017] 1. The present invention provides a prosthetic material for rhinoplasty, which has a titanium-nickel-copper alloy as the core and is coated with a plastic colloid made by mixing solid silicone rubber particles, polycarbonate ester resin, vinyl silicone resin, etc., so that the whole has good elasticity and strength, and improves the problem that silicone is not resistant to impact and is easy to deform. In addition, titanium-nickel-copper alloy has good biocompatibility, shape memory effect, relatively light specific gravity, and excellent mechanical properties. It can be used as a rhinoplasty prosthetic material to provide a stable support effect, and it can also return to its original state when impacted. In addition, the prosthesis has good biosafety and antioxidant biodegradability, and will not grow together with tissues. It can be safely implanted and removed at any time.
[0018] 2. The prosthetic material provided by the present invention not only takes into account the elasticity and strength of the prosthetic material, but also has good biocompatibility, film-forming property, isolation property and oxidation resistance. Among them, vinyl silicone resin has good film-forming property, isolation property and aging resistance; diisononyl phthalate and pentaerythritol tetra[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionate] also play an antioxidant role; polyethylene glycol-1000 plays a role in improving the dispersibility and flexibility of the resin; zinc pentachlorothiophenol, as an activation promoter, plays a protective role in shortening the mixing time of the rubber and maintaining the material performance when preparing the prosthetic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The biosafety performance diagram of rhinoplasty prosthesis materials;
[0020] Figure 2 This is a graph showing the impact resistance of rhinoplasty prosthesis materials;
[0021] Figure 3 This is the compression permanent deformation test diagram of rhinoplasty prosthesis materials. DETAILED DESCRIPTION
[0022] The technical solution described in the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0023] Example 1
[0024] The present invention also provides a method for preparing a prosthetic material for rhinoplasty, which specifically comprises the following steps:
[0025] (1) A 48% titanium, 50% nickel, and 2% copper metal wire is melted by induction heating, extruded, spun, and then heat treated at 550°C in a vacuum tube resistance furnace for 1 hour, and then slowly cooled to room temperature;
[0026] (2) 108 parts of solid silicone rubber particles were crushed and placed in a blender, and then 15 parts of polyethylene glycol-1000, 20 parts of glycerol, 23 parts of polycarbonate resin, 30 parts of methyl vinyl MQ type silicone resin, 13 parts of vinyl silicone oil, and 1.2 parts of triethylene diammonium were added, heated to 160° C., mixed evenly and stirred for 0.5 h; then 3 parts of diisononyl phthalate, 4 parts of tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionic acid] pentaerythritol, and 0.25 parts of zinc pentachlorothiophenol were added, and stirred at 150° C. for 0.5 h to obtain a mixture;
[0027] (3) The mixture obtained in step (2) is placed in a mixer and mixed at 1.2 MPa and 350°C for 0.4 h. The mixture is then transferred to the mold of step (1) to fully wrap the 66 parts of titanium-nickel-copper alloy shaped in step (1). The mixture is pressed for a second time at 30 MPa and 300°C for about 7 h. The mixture is then slowly cooled to room temperature for demolding. After sterilization, the rhinoplasty prosthesis material is obtained.
[0028] Example 2
[0029] The present invention also provides a method for preparing a prosthetic material for rhinoplasty, which specifically comprises the following steps:
[0030] (1) A 47% titanium, 50% nickel, and 3% copper metal wire is melted by induction heating, extruded, and spun, and then heat treated at 450°C in a vacuum tube resistance furnace for 1 hour. After a period of heat preservation, it is slowly cooled to room temperature;
[0031] (2) 115 parts of solid silicone rubber particles were crushed and placed in a blender, and then 22 parts of polyethylene glycol-1000, 14 parts of glycerol, 30 parts of polycarbonate resin, 36 parts of methyl vinyl MQ type silicone resin, 18 parts of vinyl silicone oil, and 0.6 parts of triethylene diammonium were added, heated to 158° C., mixed evenly and stirred for 1 hour; then 5 parts of diisononyl phthalate, 5 parts of tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionic acid] pentaerythritol, and 0.5 parts of zinc pentachlorothiophenol were added, and the mixture was stirred at 120° C. for 0.5 hour to obtain a mixture;
[0032] (3) The mixture obtained in step (2) is placed in a mixer and mixed at 1.2 MPa and 320° C. for 0.25 h. The mixture is then transferred to the mold of step (1) to fully wrap the 70 parts of titanium-nickel-copper alloy shaped in step (1). The mixture is pressed for a second time at 60 MPa and 200° C. for about 10 h. The mixture is then slowly cooled to room temperature for demolding. After sterilization, the rhinoplasty prosthesis material is obtained.
[0033] Example 3
[0034] The present invention also provides a method for preparing a prosthetic material for rhinoplasty, which specifically comprises the following steps:
[0035] (1) 50% titanium and 50% nickel metal wires are melted by induction heating, extruded, spun and shaped, and then heat treated at 600°C in a vacuum tube resistance furnace for 0.5 h. After a period of heat preservation, the wires are slowly cooled to room temperature;
[0036] (2) 90 parts of solid silicone rubber particles were crushed and placed in a blender, and then 5 parts of polyethylene glycol-1000, 22 parts of glycerol, 15 parts of polycarbonate resin, 18 parts of methyl vinyl MQ type silicone resin, 7 parts of vinyl silicone oil, and 2 parts of triethylene diammonium were added, heated to 165° C., mixed evenly and stirred for 0.25 h; then 3 parts of diisononyl phthalate, 4 parts of tetrakis[β-(3.5-di-tert-butyl, 4-hydroxyphenyl) propionic acid] pentaerythritol, and 0.1 parts of zinc pentachlorothiophenol were added, and stirred at 130° C. for 0.5 h to obtain a mixture;
[0037] (3) The mixture obtained in step (2) is placed in a mixer and kneaded at 1.2 MPa and 380°C for 0.5 h. The mixture is then transferred to the mold of step (1) to fully wrap the 60 parts of titanium-nickel-copper alloy shaped in step (1). The mixture is pressed for a second time at 20 MPa and 350°C for about 5 h. The mixture is then slowly cooled to room temperature for demolding. After sterilization, the rhinoplasty prosthesis material is obtained.
[0038] Comparative Example 1
[0039] The difference between Comparative Example 1 of the present invention and Example 1 is that there is no titanium-nickel-copper alloy inside.
[0040] Example 4
[0041] With reference to the test standard of ISO 10993-5, the biocompatibility of the material in Example 1 of the present invention was evaluated. In this experiment, the extract of the rhinoplasty prosthesis material was used to perform a biocompatibility test on human nasal epithelial cells (RPMI-2650).
[0042] RPMI-2650 was inoculated into a 96-well culture plate, with a volume of 100 μL per well and 5,000 cells per well. Then, EMEM complete culture medium (containing 90% EMEM + 10% FBS) was added to suspend the cells. The cells were then placed in a cell culture incubator at 37°C, 5% CO2, and 95% air for 24 hours. The prosthetic material of Example 1 was then immersed in the culture medium of the same concentration. After 24 hours, the culture medium was extracted and irradiated with ultraviolet light for 1 hour for standby use. At the same time, a group of culture medium was set up. The culture medium was used as the blank control group; the original culture medium of the cultured cells was aspirated, rinsed once with PBS, and 90 μL of fresh culture medium and 10 μL of extract were added to the well plate. After culturing for 24 h, 48 h, and 72 h, the original culture medium was aspirated again, washed with PBS, and then 90 μL of fresh culture medium and 10 μL of CCK-8 reagent were injected, and then incubated in the cell culture incubator for 3 h; after incubation, the absorbance at 450 nm was measured with an enzyme marker.
[0043] The results are as follows Figure 1 As shown, as the culture time increases, the activity of RPMI-2650 decreases, and when the extract of the prosthesis material with the longest culture time (72h) acts on RPMI-2650, its survival rate is still not less than 87.5%. This shows that the prosthesis material has good biosafety and can be implanted in the body.
[0044] Example 5
[0045] The materials of the above-mentioned Examples 1-3 were sliced and tested, and these test pieces were measured according to the standard ASTM E399-09 modified for prosthetic synthetic materials. The test piece dimensions were unified as 10 mm in length, 10 mm in width, and 5 mm in height. Fracture toughness 2 MPa·m 1 / 2 , fracture work 0.9×10 3 J / m 2 It is the minimum indicator for impact-resistant synthetic materials specified by ISO.
[0046] The results are as follows Figure 1 As shown, the fracture toughness of Examples 1-3 are 2.3, 2.8, and 3.1 MPa·m, respectively. 1 / 2; The fracture work is 1.6, 2.1, 2.6×10 3 J / m 2 , which are far higher than the indicators specified by ISO, indicating that the rhinoplasty prosthesis material prepared by the present invention has good impact resistance. In addition, it is found that the titanium-nickel-copper alloy with copper has higher fracture work and fracture toughness values. This also shows that the titanium-nickel-copper alloy has better mechanical properties than the copper-nickel two-phase alloy.
[0047] The prosthetic material prepared by the present invention has excellent mechanical properties, which is not only due to the presence of the titanium-nickel-copper alloy, but also the role of polycarbonate resin and vinyl silicone resin. Since polycarbonate resin itself has good toughness, oxidation resistance and impact resistance; vinyl silicone resin has good film-forming and isolation properties, and after adding vinyl silicone oil during the mixing process, the fluidity of the mixed material is further improved, so that the cured material has good hardness. In addition, polycarbonate resin and vinyl silicone resin are used as reinforcing agents for silicone rubber in the preparation of prosthetic molding, which further improves the mechanical strength of silicone rubber.
[0048] Example 6
[0049] The prosthetic materials of the above-mentioned Examples 1-3 and Comparative Example 1 were sliced and subjected to a compression permanent deformation test according to the A test method of ASTM D395-03 (pressure permanent deformation under constant force in air). The test pieces had uniform dimensions of 6 mm in thickness, 13 mm in diameter, 30% in compression rate, 72 h in compression time, and 100°C in experimental temperature.
[0050] The results are as follows Figure 3 As shown, the compression permanent deformation rates of Examples 1-3 and Comparative Example 1 are 17.7%, 18.4%, 20.1%, and 29.8%, respectively. Compared with Comparative Example 1, the prosthetic materials prepared in Examples 1-3 exhibit excellent anti-compression deformation capability, which can be attributed to the memory effect of the titanium-nickel-copper memory alloy, which makes the prosthetic material have excellent recoverable elasticity and is not easily deformed.
[0051] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the principle of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A rhinoplasty prosthesis material with a titanium-nickel-copper alloy as the core, characterized in that: Made of the following components in parts by weight: 66 parts of titanium-nickel-copper alloy, 108 parts of solid silicone rubber particles, 23 parts of polycarbonate resin, 30 parts of methyl vinyl MQ type silicone resin, 13 parts of vinyl silicone oil, 1.2 parts of triethylene diammonium, 20 parts of glycerol, 15 parts of polyethylene glycol-1000, 3 parts of diisononyl phthalate, 4 parts of tetrakis[β-(3,5-di-tert-butyl, 4-hydroxyphenyl) propionate] pentaerythritol, 0.25 parts of zinc pentachlorothiophenol, wherein the alloy contains 50% nickel, 48% titanium and 2% copper; The method for preparing a rhinoplasty prosthesis material with a titanium-nickel-copper alloy as a core comprises the following steps: (1) A 48% titanium, 50% nickel, and 2% copper metal wire is melted by induction heating, extruded, spun, and then heat treated at 550°C in a vacuum tube resistance furnace for 1 hour, and then slowly cooled to room temperature; (2) 108 parts of solid silicone rubber particles were crushed and placed in a blender, and then 15 parts of polyethylene glycol-1000, 20 parts of glycerol, 23 parts of polycarbonate resin, 30 parts of methyl vinyl MQ type silicone resin, 13 parts of vinyl silicone oil, and 1.2 parts of triethylene diammonium were added, heated to 160° C., mixed evenly and stirred for 0.5 h; then 3 parts of diisononyl phthalate, 4 parts of tetrakis[β-(3,5-di-tert-butyl, 4-hydroxyphenyl) propionic acid] pentaerythritol, and 0.25 parts of zinc pentachlorothiophenol were added, and stirred at 150° C. for 0.5 h to obtain a mixture; (3) The mixture obtained in step (2) is placed in a mixer and mixed at 1.2 MPa and 350°C for 0.4 h. The mixture is then transferred to a mold and the 66 parts of titanium-nickel-copper alloy shaped in step (1) are fully wrapped therein. The mixture is pressed for a second time at 30 MPa and 300°C for 7 h. The mixture is then slowly cooled to room temperature for demolding and sterilized to obtain the rhinoplasty prosthesis material.
2. A method for preparing a rhinoplasty prosthesis material with a titanium-nickel-copper alloy as a core as claimed in claim 1, characterized in that: The steps include: (1) A 48% titanium, 50% nickel, and 2% copper metal wire is melted by induction heating, extruded, spun, and then heat treated at 550°C in a vacuum tube resistance furnace for 1 hour, and then slowly cooled to room temperature; (2) 108 parts of solid silicone rubber particles were crushed and placed in a blender, and then 15 parts of polyethylene glycol-1000, 20 parts of glycerol, 23 parts of polycarbonate resin, 30 parts of methyl vinyl MQ type silicone resin, 13 parts of vinyl silicone oil, and 1.2 parts of triethylene diammonium were added, heated to 160° C., mixed evenly and stirred for 0.5 h; then 3 parts of diisononyl phthalate, 4 parts of tetrakis[β-(3,5-di-tert-butyl, 4-hydroxyphenyl) propionic acid] pentaerythritol, and 0.25 parts of zinc pentachlorothiophenol were added, and stirred at 150° C. for 0.5 h to obtain a mixture; (3) The mixture obtained in step (2) is placed in a mixer and mixed at 1.2 MPa and 350°C for 0.4 h. The mixture is then transferred to a mold and the 66 parts of titanium-nickel-copper alloy shaped in step (1) are fully wrapped therein. The mixture is pressed for a second time at 30 MPa and 300°C for 7 h. The mixture is then slowly cooled to room temperature for demolding and sterilized to obtain the rhinoplasty prosthesis material.
Citation Information
Patent Citations
Methods of sterilizing polycarbonate articles
CN101005860A
Elastic prosthetic material and preparation method thereof
CN107519532A
Nasal plastic prosthesis
CN215307035U
Shape memory alloy for living body
JP3013384B2
